Novel immobilization method of Lactiplantibacillus plantarum in grains for dry food products - Karwowski, Marilia Silva Malvezzi (Food science and technology international = Ciencia y tecnologia de los alimentos internacional, 2024)
This study aimed to assess the potential use of grains (amaranth, millet, and quinoa) as immobilizing matrices on the metabolic activity of Lactiplantibacillus plantarum and evaluate the viability of the probiotic immobilized in millet during simulated oro-gastrointestinal digestion (OGI) and storage. Firstly, different grains, sterilization and immobilization times were assessed. Secondly, Lp. plantarum was immobilized in millet and its viability and metabolic activity were assessed during non-refrigerated long-term storage and OGI. Metabolic activity was higher with 15 min. of grain sterilization and 72 h of immobilization. Lp. plantarum in millet showed the highest count. Millet grains were able to maintain the high population (>7 log CFU/g) and the metabolic activity of Lp. plantarum during up to 150 d of storage and conferred a protective effect on entrapped probiotic cells during OGI. Millet is a promising immobilizing matrix for the addition of probiotics in dry food products